Prolonged survival in motor neuron disease: a descriptive study of the King's database 1990–2002. Issue 7 (1st July 2003) - Turner, M R; Parton, M J; Shaw, C E; Leigh, P N; Al-Chalabi, A
Abstract : Motor neuron disease is a clinically heterogeneous disease with significant differences in survival. The authors have characterised a subset of long term survivors seen in a tertiary clinic over a 12 year period in terms of clinical variables and demographics, comparing them with short term survivors and the remaining population. Thirty of 769 patients survived more than 10 years, corresponding to 4% of the total population. Significantly younger onset of disease symptoms and a predominance of pure upper motor neuron signs at presentation characterised the long term survivors, but factors traditionally regarded as being associated with poor prognosis were also well represented. For a few people with motor neuron disease there remains the hope, whatever the initial presentation, that their subsequent survival will be longer than expected.